Cultural field and the Amauta Publishing Society. The other adventure of José Carlos Mariátegui - Gonzales Alvarado, Osmar (2021)
In the following pages, the author describes and analyzes the role of the Sociedad Editora Amauta founded in Lima in 1926 by brothers José Carlos and Julio César Mariátegui, both to influence the intellectual, artistic and ideological debate and to impact the littler expanded market of the printed object, thanks to the printing of the Amauta magazine and a set of books, mainly. To achieve their goals, the business brothers would weave a wide network of agents distributed throughout much of the national territory, as well as a system of alliances with some foreign publisher and authors.